Analisis Motivasi Belajar Siswa melalui Pembelajaran Berbasis Masalah dengan Pendekatan CRT - Isma, Nafiatul; Azizah, Mira; Antoko, Ladung (JURNAL PENA EDUKASI, 2025)
Abstract: The study aims to analyze students' motivation for learning through problem-based learning with the culturally relevant teaching (CRT) approach in elementary schools. This study uses a mixed methods approach, integrating quantitative and qualitative methods to understand students' learning motivation better. The quantitative method uses a questionnaire to measure students' motivation levels before and after implementing problem-based learning with the CRT approach. In contrast, the qualitative method is carried out through in-depth interviews and observations to explore students' perceptions of their experiences in problem-based learning that is sensitive to their cultural context. The study results indicate that implementing problem-based learning with the Culturally Relevant Teaching (CRT) approach has succeeded in increasing the learning motivation of fifth-grade students of SDN Sawah Besar 01. This is indicated by an increase in the average learning outcome score from 62 in the pre-test to 78 in the post-test. Overall, the results of this study indicate that problem-based learning with the CRT approach can be an effective alternative to increase students' learning motivation in fifth-grade students of SDN Sawah Besar 01.Keywords: Culturally Relevant Teaching; learning motivation; problem-based learning. Abstrak: Penelitian bertujuan untuk menganalisis motivasi belajar siswa melalui pembelajaran berbasis masalah dengan pendekatan Culturally Relevant Teaching (CRT) di sekolah dasar. Penelitian ini menggunakan pendekatan gabungan (mixed methods), yang mengintegrasikan metode kuantitatif dan kualitatif untuk memperoleh pemahaman yang lebih komprehensif tentang motivasi belajar siswa. Metode kuantitatif dilakukan dengan menggunakan angket untuk mengukur tingkat motivasi siswa kelas V A yang berjumlah 27 siswa sebelum dan setelah penerapan pembelajaran berbasis masalah dengan pendekatan CRT, sementara metode kualitatif dilakukan melalui wawancara mendalam dan observasi untuk menggali persepsi siswa tentang pengalaman mereka dalam pembelajaran berbasis masalah yang sensitif terhadap konteks budaya mereka. Hasil penelitian menunjukkan bahwa penerapan pembelajaran berbasis masalah dengan pendekatan CRT berhasil meningkatkan motivasi belajar siswa kelas V SDN Sawah Besar 01. Hal ini ditunjukkan dengan peningkatan rata-rata skor hasil belajar dari 62 pada pre-test menjadi 78 pada post-test. Secara keseluruhan, hasil penelitian ini menunjukkan bahwa pembelajaran berbasis masalah dengan pendekatan CRT dapat menjadi alternatif yang efektif untuk meningkatkan motivasi belajar siswa di kelas V SDN Sawah Besar 01.Kata kunci: Culturally Relevant Teaching; motivasi belajar; pembelajaran berbasis masalah.